Self-Selected and Prescribed Intensity Exercise to Improve Physical Activity Among Inactive Retirees - Zhinan Yang (2018)
© The Author(s) 2018. A randomized controlled study explored the effects of two intensity-oriented exercise interventions on affect to exercise and physical activity behavior. Inactive retirees finished the 12-week group-based exercise intervention and 3-month telephone follow-up with 27 in self-selected intensity group and 26 in prescribed intensity group. Repeated measures of daily step counts (measured by Yamax pedometers), positive and negative affect to exercise, weight, height, waist circumference, and blood pressure were done at baseline, postintervention, and 3-month follow-up. Increased daily step counts and positive affect, and reduced body mass index, waist circumference, blood pressure of both groups, and negative affect of self-selected intensity group were found at different measuring times. Although self-selected intensity group had no significantly different daily step counts from prescribed intensity group, the former had a more positive and less negative affect to exercise. Findings suggest that future exercise programs use self-selected intensity exercise programs to improve pleasure affect to exercise.